Optimasi Parameter Pembubutan Terhadap Kekasaran Permukaan Produk - Utami Dewi, Franscisca Gayuh; Gapsari, Femiana (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
Machining parameters in turning processes including cutting speed, depth of cut, feed rate, and the length of the cutting parameters affect the product quality. One of the required product quality is the level of surface roughness. Reseach used response surface experimental based on central composite design to develop the empirical method of relationship between cutting parameters and surface roughness. Furthermore, an optimization is also conducted by using desirability function approach to determine the combination of cutting parameters in order to have low surface roughness of product. The results show that the machining parameters (depth of cut, length of cutting, cutting speed) have significant impact to the surface roughness of product. Based on the results, the mathematical model: Y = 1.109 -0.068(X ) – 0.111(X 2 )-0.098(X 3 ) + 0.268 (X 1 ) 2 + 0.17 (X 2 ) 2 + 0.106 (X 3 ) 2 + 0.086X 1 X 2 - 0.073XKeywords: surface roughness, machining, depth of cut, cutting speed.